National Altitude Training Centre
The National Altitude Training Centre at Silver Star Mountain Resort is the only facility of its kind in Canada. Operating on a year round basis, the training centre offers comprehensive training and testing to all levels of individual and team athletes. Already associated with Cross Country Canada and Biathlon Canada, the Sports Science Department at the training centre is researching and developing new methods to improve the sports performance of the elite and recreational athlete. Located 1915 Metres, (6280 ft) above sea level and has a vertical hieght of 760 metres (2500 ft), in Silver Star Mountain Resort's unique village community, the 1,200 square foot training centre houses weight training and physio/massage facilities, the Sports Medicine/Science Department, testing equipement, office space, locker rooms and equipment storage. The multi-purpose activity room accommodates up to 225 people and is designed to function as a lecture theatre or aerobic workout room. In addition, an outdoor paved track provides 6 plus km for roller skiing, and 30 km of track available for cross-country skiing in the winter months, and for running or mountain biking in the summer. Village amenities, including restaurants and accommodation, are within easy walking distance of the training centre and different recreational activities are available depending on the season. If training is a priority for you or your team, the National Altitude Training Centre will provide all the facilities you need. Group or individual packages including meals, accommodation with use of facilities and services can be designed specifically to suit your needs.